Representasi Islam pada Bangunan Museum Islam K.H. Hasyim Asy’ari - Izza Nurul Imada; Nafisah Nafisah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Abstract This study examines the representation of Islam in the architecture of the KH Hasyim Asy'ari Indonesian Islamic Museum as a symbol of preserving Islamic history and culture in Indonesia. Using a descriptive qualitative method, this study identifies the symbolic and philosophical elements contained in the facade, interior, and circulation of the museum space. The results of the study show that the museum architecture adopts a post-modern style with a triangular pyramid shape that tapers upwards, symbolizing the majesty and sustainability of Islamic civilization. The concept of postmodern space is applied, with unclear boundaries between spaces, creating a continuous visual and functional flow, while providing a harmonious spatial experience for visitors. The arrangement of space and circulation utilizes the principle of postmodern space, where spaces appear separate but remain visually and functionally connected, reflecting diversity and inclusivity in the concept of Islam. The representation of Islam on the museum facade is depicted through a motif that resembles santri sungkem to kyai, a symbol of respect and closeness to religious teachings. The pyramid shape not only adopts world architectural designs, but also has a philosophical meaning related to the majesty, identity, and heritage of Islamic civilization in Indonesia. This study confirms that museum architecture is not only a work of visual art, but also a symbol of Islamic identity that is profound and historically and culturally meaningful.